EMOTION VERBS IN BAHASA INDONESIA AND ASAHAN MALAY LANGUAGE: CROSS-LANGUAGE SEMANTICS ANALYSIS - Mulyadi, Mulyadi; Beratha, Sutjiati; Okatavianus, Oktavianus (e-Journal of Linguistics, 2012)
This research aims to compare the semantics of emotion verbs in Indonesian (EVI) and that in Asahan Malay (EVAM). The problems under study cover (1) the parameters of emotion verbs, (2) the construction of emotion verbs, (3) the categorization of emotion verbs, (4) the meaning of emotion verbs, and (5) the semantic roles of arguments for emotion verbs.             With formal parameters, emotion verbs were tested by using (1) transitive, (2) interrogative, (3) progressive, (4) adverbia dengan sengaja ‘deliberately’, and (5) reflexive. The semantic test was employed by using the component ‘X merasakan sesuatu karena X memikirkan sesuatu’ (X felt something because X thought something). In the causative contruction, EVI form dative-experiencer pattern marked with a preposition. EVI and EVAM can be subcategorized into stative-active emotion verbs. The difference of their components covers (1) sedih vs sodih , (2) khawatir vs gopoh ,  (3) terpukau vs tabodoh , (4) lega vs tonang , dan (5) frustrasi vs suntuk . The meaning of EVI and EVAM are different in terms of their element or (sub-) component. For SEV, the difference in meaning was found in the verbs (1) sedih vs sodih , (2) susah vs susah , (3) takut vs cuak , (4) khawatir vs gaduh ,  (5) risau vs riso , (6) gugup vs gopoh , (7) panik vs tagomap , (8) malu vs malu , (9) segan vs sogan , (10) kaget and terkejut vs takojut , and (11) terpukau vs tabodoh . Meanwhile, for AEV, the meaning difference was found in the verbs (1) gembira and girang vs mogah , (2) lega vs tonang , (3) frustrasi vs suntuk , (4) iri vs angek , (5) jenuh and jemu vs jolak , (6) jengkel vs  palak and rising , and (7) keki vs marsak . SEV require undergoer for the subject. For AEV, the subject is the actor, and the object is the undergoer. The difference of thematic relations in the two languages was found in the emotion verbs jengkel (BI) and rising (BMA).
Keywords: emotion verbs, semantic components, categorization, meaning, and semantic roles